A sequential targeting strategy interrupts AKT-driven subclone-mediated progression in glioblastoma - Kebir, Sied; Herold-Mende, Christel; Scheffler, Björn (Clinical cancer research, 2023)
Therapy resistance and fatal disease progression in glioblastoma are thought to result from the dynamics of intra-tumor heterogeneity. This study aimed at identifying and molecularly targeting tumor cells that can survive, adapt, and subclonally expand under primary therapy.To identify candidate markers and to experimentally access dynamics of subclonal progression in glioblastoma, we established a discovery cohort of paired vital cell samples obtained before and after primary therapy.
Online veröffentlicht am 14. Oktober 2022
Gesehen am 28.11.2023